Μελέτη φιλικών προς το περιβάλλον αντιρρυπαντικών επιστρωμάτων για τη βελτίωση της ενεργειακής αποδοτικότητας των πλοίων - Κιοσίδου, Ευαγγελία (Σχολή Ναυπηγών Μηχανολόγων Μηχανικών, 2018)
In the present PhD thesis, commercial and experimental antifouling painting systems were examined, in terms of antifouling, anticorrosion and hydrodynamic efficiency and with regard to their mechanical and physical properties. The examined paints were of silicone, polyurethane (PU) and acrylic formulations. Five antifouling (AF) systems were tested, while also an anti-corrosive system, without antifouling effect, was examined for comparative purposes. The experimental formulations were developed in the framework of the FP7 European Collaborative Project Foul-X-Spel (Grant Agreement 285552). Anticorrosion assessment was performed through accelerated aging tests, namely salt spray tests (ISO 14993:2001), UV tests (ASTM G 154-06) and immersion in artificial seawater at room temperature.The objective of these experiments was to determine the barrier properties of each painting system in intact state using electrochemical impedance spectroscopy (EIS). In addition, optical and mechanical properties were examined. Experiments on painted steel samples with scribes were performed for 12 weeks in salt spray exposure. The aim of this test was to examine the barrier properties that the unscratched part of the paint provides. The observed rust morphology in the area of the scribes was correlated with the paint efficiency and a ranking between the examined painting systems was performed. Rust morphology characterization was performed through XRD, Raman spectroscopy and SEM observation. The next step of this study included electrochemical examination of the rusted, scribed specimens at 6, 8 and 12-week intervals and included EIS and linear polarization resistance (LPR) methods. Fitting of the experimental impedance curves was performed through Particle Swarm Optimization and Complex Non-Linear Least Squares Fitting procedures and for a selected number of representative diffusion models, which could potentially describe the mode of corrosion during the course of the salt spray experiment. Antifouling assessment included static immersion tests in Elefsis Gulf for one year. Six (6) specimens per painting system were immersed in the field. Every two months a specimen was removed from site and examined in the laboratory, in terms of fouling density, types of foulers and physical damage of the paint. Periodic examination included also measurement of the barrier properties of the coated steel samples using EIS, while also optical and mechanical properties were examined. Hydrodynamic tests included flat plate resistance tests in three conditions: smooth, painted with each one of the examined antifouling coating systems (arbitrary roughness) and covered with sandpapers of 40 and 80-grit size (homogeneous roughness). The experiments were performed in the experimental towing tank of the Laboratory of Ship and Marine Hydrodynamics (LSMH) at various speeds (or Reynolds numbers) and drag measurements for each case were performed, in order to compare the drag effect caused by each condition. Examination of the painting systems in terms of mechanical and physical properties included water-liquid transmission rate, cupping, chalking and dirt pick up tests, according to the corresponding stabdards (ISO/ASTM). The investigation performed during the present thesis intended to offer a thorough analysis for a comprehensive assessment of the effciency of commercial and experimental antifouling (or organic, in general) paints. (en) (el)